2008
DOI: 10.1111/j.1463-1326.2008.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic symptoms, treatment satisfaction, adherence and their associations with glycaemic goal in patients with type 2 diabetes mellitus: findings from the Real‐Life Effectiveness and Care Patterns of Diabetes Management (RECAP‐DM) Study

Abstract: Patients' reports of hypoglycaemic symptoms are common in European outpatients with type 2 diabetes and are associated with significantly lower treatment satisfaction and with barriers to adherence. In addition, being at HbA1C goal is associated with treatment satisfaction and adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
4
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 29 publications
11
97
4
7
Order By: Relevance
“…Similar results were obtained by Alveres-Guisasola et al in the RECAP study [27], where hypoglycaemia episodes were found in 38% of patients, including severe ones in 5%, and by Tłuczykont et al -hypoglycaemia [19]. Indeed, as evidenced by Bodmer et al, the highest risk of hypoglycaemia is present during insulin treatment (14.9%) [28].…”
Section: Discussionsupporting
confidence: 76%
“…Similar results were obtained by Alveres-Guisasola et al in the RECAP study [27], where hypoglycaemia episodes were found in 38% of patients, including severe ones in 5%, and by Tłuczykont et al -hypoglycaemia [19]. Indeed, as evidenced by Bodmer et al, the highest risk of hypoglycaemia is present during insulin treatment (14.9%) [28].…”
Section: Discussionsupporting
confidence: 76%
“…Hypoglycemia in people with type -2 diabetes or fear of hypoglycemia creates difficulties in managing everyday life and might decrease quality of life [12][13][14][15][16]. Related data of current study is limited, although participants expressed fatigue and a feeling of not being able to perform tasks satisfactorily.…”
Section: Restrictions In Daily Life Related To Hypoglycemiamentioning
confidence: 72%
“…This in turn can present an obstacle to optimizing the blood glucose balance [11]. People who have repeated hypoglycemia problems reported a lower quality of life, less treatment satisfaction, and were more depressed than people not suffering from hypoglycemia [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…El nivel de conocimiento de los pacientes sobre la enfermedad y la medicación influye en el cumplimiento [7][8][9][10][11][12], la calidad de vida y el grado de satisfacción [13], mientras que una baja satisfacción con el tratamiento repercute en el cumplimiento terapéutico, el número de episodios de hipoglucemia y niveles de hemoglobina glicosilada (HbA1c) [14].…”
Section: Introductionunclassified